Analisis Strategi Konten dan Opini Publik Terhadap Kajian Dakwah Isu Keluarga Ustadz Hilman Fauzi - Eka Octalia Indah Librianti; Dede Mercy Rolando; Muhammad Abduh (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2026)
This study aims to analyze the content strategy and public opinion regarding da'wah on family and women's issues delivered by Ustadz Hilman Fauzi through the TikTok platform. The study uses a qualitative method with a netnographic approach, with primary data sources in the form of da'wah video content and secondary data sources in the form of audience comments. Data analysis techniques include content analysis and public sentiment analysis by categorizing sentiments into positive, neutral, and negative categories, using sentiment measurement tools such as Tolos, Brand24, and Collabas Research on more than 27,000 comments from five trending videos.The results of the study indicate that Ustadz Hilman Fauzi's da'wah strategy is effective because it adopts an empathetic healing da'wah approach, focuses on a universal and evergreen family niche, and is able to optimize TikTok's characteristics and algorithms through short video formats, varied visuals, and consistent uploads. Sentiment analysis shows the dominance of neutral sentiment (70%) and positive sentiment (30%), indicating broad public acceptance without causing polarization. These findings confirm that contextual, humanistic, and strategic digital da'wah is capable of building engagement and ensuring the sustainability of da'wah on social media.